Dengue vaccines: the road to failure or to success? - Stanley A. Plotkin (Taylor & Francis Group, 2020)
A licensed vaccine against dengue was shown to enhance disease under some circumstances, even though it protected most vaccinees. We discuss the implication of these results for the future of dengue vaccines.